A MODULE OF A GEOINFORMATION SYSTEM BASED ON NUMERICAL MODELING OF INVERSE PROBLEMS OF GEOCHEMISTRY BY REGULARIZING ALGORITHMS - Temirbekova Л.Н.; Temirbekov Н.М.; Los В.Л.; Imangaliyev Е.И.; Baigereyev Д.Р; Nurmangalieva М.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Currently, due to the rapid development of computer technology in geology, methods and approaches of scientific visualization based on additional data analysis are being intensively developed. The general concept is that the main data field on the daily surface and additional conditions are set at the input. Further, methods of mathematical geophysics are used for their analysis and processing, as a result of which new information is obtained for deep surveys. Then, in the information system, visualization tools are applied to the new information received and to the main data field. Thus, the information system is based on the synthesis of visual representation methods and methods of mathematical geophysics, computational mathematics from different branches of knowledge. This paper presents a description of the software module of the geoinformation system, based on the methods of intelligent detection of anomalies of hidden deposits, for deep predictive and search modeling of deposits. The functioning of the software module is based on the application of the theory of inverse problems of mathematical geophysics with elements of artificial intelligence using geological data on the earth’s surface, geophysical measurements and geochemical analyses as input data. The program module for the inverse problem of the continuation of potential fields in the direction of disturbing masses is used for real data of a specific mineral deposit.